Braking Control Strategy of Four-wheel-drive Electric Vehicles Considering Braking Intention Recognition - Pan Gongyu; Wang Xuepan (Jixie chuandong)
In order to improve the braking energy recovery rate, the braking effect required by drivers with different braking intentions under different working conditions is considered, and a braking control strategy of four-wheel-drive electric vehicles is proposed. Firstly, according to conventional braking conditions, control strategies are designed from the perspectives of braking energy recovery rate, stability and safety based on conventional braking intention recognition. Secondly, according to different coasting braking intentions under coasting conditions, whether and when the electric force intervenes are determined, and the size of the braking force from motors is calculated according to the driver's required coasting distance. Thirdly, the external characteristics of the front and rear motors are obtained by bench tests, and the optimal utilization efficiency model of the front and rear motors is established. Finally, Carsim and Simulink are used for co-simulation analysis. The results show that the braking energy recovery rate is improved by 13.64 percentage points compared with the parallel control strategy in new European driving cycle （NEDC） condition. It can effectively identify the driver's required coasting distance under coasting conditions and improve the vehicle's coasting economy.